21
42
63
18
Correct answer is B
Let f(p) = 6p3 - p2 - 47p + 30
Then by the remainder theorem,
(p - 3): f(3) = remainder R,
i.e. f(3) = 6(3)3 - (3)2 - 47(3) + 30 = R
162 - 9 - 141 + 30 = R
192 - 150 = R
R = 42
The shaded portion in the diagram is the solution of...
If (x - a) is a factor of bx - ax + x2 - ab, what is the other factor?...
If P and Q are two statements, under what condition would p|q be false? ...
make u the subject in x =2u−33u+2...
The diagram shows a circle O. If < ZYW = 33o , find < ZWX ...
A student blows a balloon and its volume increases at a rate of π(20 - t2)cm3S-1 after t secon...
In the diagram above, O is the centre of a circle NST. |NT| = |ST| and ∠NTS = 36°. Find the ...
In △ XYZ, XY = 13cm, YZ = 9cm, XZ = 11cm and XYZ = θ. Find cosθo...